The influence of natural environment in residential areas on subjective well-being of the elderly - Li, Zhen; Jiang, Yi; Jin, Ziyang; Pu, Yiran; Li, Hao (Frontiers in Public Health, 2023)
Objectives The aim of this study is to explore the relationship between the natural environment of residential areas and the subjective wellbeing of the elderly and the role of elderly's evaluation of the government's environmental protection work in both. Methods Based on the China Social Survey Database in 2013, 2015, 2017, 2019, Stata were used to process the data screened according to the restricted conditions. Ordered Probit Model and Sobel were used to test the effect relationship among the variables. Results The subjective wellbeing of the elderly is roughly increasing. The natural environment of the living area has a significant positive effect on the subjective wellbeing of the elderly. The evaluation of the elderly on the government's environmental protection work has a positive impact on the elderly's subjective wellbeing similarly and plays an increasingly important intermediary role in the impact of the natural environment in the residential area on the elderly's subjective wellbeing. Conclusion To improve the subjective wellbeing of the elderly, the government should continue to play a leading role in coordinating environmental protection and pollution control, strengthen publicity of environmental protection work. Moreover, improve the residential environment governance and protection system oriented by the elderly's evaluation of the government's environmental protection work.